Pengelolaan Keuangan dan Peran Wanita dalam Pengambilan Keputusan Ekonomi di Dusun Bukur Kecamatan Selopuro Kabupaten Blitar - Triana, Endang Shyta; Hendrawardani, Blandina; Uswatun Khasanah (JURNAL ILMIAH EDUNOMIKA, 2025)
This research explores the role of women in economic decision making in Bukur Village, East Java, with a focus on their dual responsibilities as caregivers and managers of family finances. This research aims to analyze how demographic factors, such as age and education, influence women's roles in financial management and economic decisions, while considering the impact of patriarchal culture on their participation. This research utilizes quantitative data by using quantitative descriptive research by means of a survey, distributing questionnaires to respondents to measure variables in research on a population or sample. This research relies on primary data collected directly from participants involved in the research. The answer instrument items use a Likert Scale, then tabulated and then processed using SPSS. The partial research results show that the variables of the role of women and financial management have an influence on decision making and simultaneously/together have a significant influence on the decision making variables. Productive age (25-50 years) and education are determining factors in economic decision making. Keywords: The Role of Women, Financial Management, Decision Making, Productive Age, Patriarchal Culture